PENGARUH PENGALAMAN AUDIT, INDEPENDENSI, BEBAN KERJA, TIPE KEPRIBADIAN DAN SKEPTISME PROFESIONAL AUDITOR TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN (Studi Empiris pada KAP di Kota pekanbaru, Padang dan Medan) - Indah Novita; Emrinaldi Nur DP; Rofika Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study examines the factors that influence of audit experience,independence, workload, types of personality and professional skepticism auditorto Fraud Detection Ability of Auditors at Accounting Public Office in Pekanbaru,Padang and Medan. Respondents in this study is the auditor who works for thepublic accounting firms in Pekanbaru, Padang and Medan. The data collection isdone by distributing questionnaires directly to the auditor about 136 copies andonly 90 were returned. The sampling method is by using purposive sampling,while data processing using SPSS as software for data processing. Results of theresearch show that audit experience, independence, workload, types ofpersonality and professional skepticism auditor have a significant effect onchanges in value of the Fraud Detection Ability of Auditors. The modeldetermination coefficient is 0.873. It means that 87.3% changes in the value of theindependent variable audit experience, independence, workload, type s ofpersonality and professional skepticism auditor affect the dependent variables theauditor's ability to detect fraud. The remaining 12.7% changes in dependentvalues are influenced by other variables not in the model. Partially the auditexperience, independence, workload, personality type and professional skepticismof the auditor influence the auditor's ability to detect fraud.Keywords : audit experience, independence, workload, types of personality,professional skepticism auditor, Fraud Detection Ability of Auditor